Antropologi dan Pelayanan Publik: Meningkatkan Pengalaman Pelanggan Bas Persiaran di Malaysia Melalui Kearifan Lokal - Satiadharmanto, Deddi Fasmadhy; Satriyo, Bagus; Lailatul Fitriyah, Fahma; Agia Firmansyah, Viky; Indah Widiyawati, Tutut; Huda, M. Dimyati; Muhammd Syamsul Azam, Bagus (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2024)
Quality public service is crucial in enhancing customer experience, especially in the tourism sector. This study aims to explore how local wisdom can be integrated into Bas Persiaran services in Malaysia to improve customer satisfaction. The methods used in this community service initiative include training for drivers on local wisdom values and friendly, responsive service techniques to meet tourists' needs. The results indicate a significant increase in customer satisfaction, reflected in positive feedback regarding service quality and overall experience while using Bas Persiaran. The application of local wisdom in service not only strengthens the positive image of Bas Persiaran but also enhances social relationships between drivers and passengers, creating a more memorable travel experience. This research is expected to serve as a reference for Bas Persiaran managers to enhance service quality and customer satisfaction in the future.